A comparison of one-stage posterior hemivertebrectomy and asymmetric osteotomy combined with posterior release for young children with congenital scoliosis - Jiang Cao; Song Yu; Xin Lv; Lin Chen; Tangjiang Li; Limei Luo (European Journal of Medical Research)
Abstract Background This study aimed to assess the efficacy and complications of one-stage posterior hemivertebrectomy and asymmetric osteotomy combined with posterior release in treating congenital scoliosis among young children. Methods The retrospective study comprised 30 patients with congenital scoliosis who were admitted between January 2016 and May 2023. The control group consisted of 15 patients who received standard posterior osteotomy with posterior release, while the study group consisted of the remaining 15 patients who underwent one-stage posterior hemivertebrectomy. The perioperative metrics, treatment outcomes, lumbar–thoracic function, quality of life, and complications between the two groups were compared. Results The study group showed better outcomes than the control group in terms of the duration of surgery, intraoperative blood loss, and length of hospital stay (P < 0.05). The study group had lower values for the thoracic Cobb angle, the lumbar Cobb angle, and the distance from the midpoint of C7 to the sacral vertical line (C7–CSVL) than that of the control group. (P < 0.05). In terms of the SRS-22 score and Oswestry Disability Index evaluation, the study group outperformed the control group (P < 0.05). The incidence rate of complications was lower in the study group than in the control group (P < 0.05). Conclusion Posterior hemivertebra resection significantly improves the treatment outcomes for young children with congenital scoliosis. It can shorten the duration of surgery, reduce intraoperative blood loss and the length of hospital stay, decrease the thoracic and lumbar Cobb angles, rapidly restore lumbar–thoracic function, enhance the quality of life, and has fewer complications.